The Impact of Increased Cost-Sharing on Utilization of Low Value Services: Evidence from the State of Oregon - Jonathan Gruber; J. Catherine Maclean; Bill Wright; Eric Wilkinson; Kevin G. Volpp (Institute of Labor Economics (IZA), 2017)
In this study we examine the impact of a value-based insurance design (V-BID) program implemented between 2010 and 2013 at a large public employer in the state of Oregon. The program substantially increased cost-sharing, specifically copayments and coinsurance, for several healthcare services believed to be of low value and overused (sleep studies, endoscopies, advanced imaging, and surgeries). Using a differences-in-differences design coupled with granular, administrative health insurance claims data, we estimate the change in low value healthcare service utilization among beneficiaries before and after program implementation relative to a comparison group of beneficiaries who were not exposed to the V-BID. Our findings suggest that the V-BID significantly reduced utilization of targeted services. These findings have important implications for both public and private healthcare policies as V-BID principles are rapidly proliferating in healthcare markets.
Keywords: I1; I11; I18; 330; healthcare; low value; value-based insurance design; cost-sharing